1992
DOI: 10.1002/ajh.2830400405
|View full text |Cite
|
Sign up to set email alerts
|

Phorbol ester‐induced hairy cell features on chronic lymphocytic leukemia cells in vitro

Abstract: Leukemic cells from eight patients with chronic lymphocytic leukemia were isolated and cultured in the continuous presence of 12-O-tetradecanoylphorbol 13-acetate (TPA) at a concentration of 1.6 x 10(-9) M for 4-10 days. Aliquots of cells were then analyzed at intervals of 24-72 hr for changes in morphology, acid phosphatase staining (AP), and expression of two hairy cell-associated surface antigens, HCL1 (CD22, Leu 14) and HCL3 (CD11c, Leu M5). All cases studied showed typical B-CLL phenotype, and only a smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…Phorbol esters have been reported to induce differentiation of CLL cells. 37 Bryostatin 1 is a structurally related compound lacking the tumor-promoting effects of phorbol esters. Bryostatin 1 induces morphological changes in CLL, including an increase in cell size, irregularity in cell shape, and formation of cytoplasmatic extensions ( Figure 1A).…”
Section: Discussionmentioning
confidence: 99%
“…Phorbol esters have been reported to induce differentiation of CLL cells. 37 Bryostatin 1 is a structurally related compound lacking the tumor-promoting effects of phorbol esters. Bryostatin 1 induces morphological changes in CLL, including an increase in cell size, irregularity in cell shape, and formation of cytoplasmatic extensions ( Figure 1A).…”
Section: Discussionmentioning
confidence: 99%
“…Bryostatin also appears to enhance fludarabine induction of apoptosis of leukemia cells [19]. Treatment of CLL cells in vitro with bryostatin alters the morphology and the phenotype to resemble hairy cells [22]. A series of studies are evaluating combinations of bryostatin with purine analogues.…”
Section: Bryostatinmentioning
confidence: 98%
“…348 This drug has been shown to induce terminal differentiation of B-cell morphology and a phenotype resembling hairy cell leukemia. 349,350 Preclinical studies have suggested a synergistic action between bryostatin and purine analogues or interferon alfa. [351][352][353] Flavopiridol, a cyclin-dependent kinase (CDK) inhibitor, causes cell cycle inhibition at G 1 and G 2 M 354,355 and rapidly induces apoptosis in a cell cycle-and p53-independent manner.…”
Section: New Drugsmentioning
confidence: 99%